ANALISIS PEMAHAMAN KONSEP OPERASI BILANGAN BULAT SISWA KELAS VII SMP MELALUI PENGGUNAAN ALAT PERAGA PAPAN OBIBIUL - Efi Ismauliani; Elza Elfira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze seventh-grade junior high school students’ conceptualunderstanding of integer operations through the use of the OBIBIUL (IntegerOperations) board. This study employs a descriptive qualitative approach with acase study design. The research subjects consisted of two seventh-grade juniorhigh school students selected purposively based on their mathematical ability levels,namely students with high and low abilities. Data collection was conducted throughobservation, interviews, and documentation of the use of the OBIBUL Boardteaching aid. The results of the study indicate that the use of the OBIBUL Boardteaching aid can help improve students’ conceptual understanding of integeroperations in a tangible and meaningful way. Students were able to understand theconcepts of addition, subtraction, multiplication, and division of integers in a morevisual and structured manner. This teaching aid also encouraged students’ activeengagement in the learning process, making the concepts easier to understand andremember. This study highlights the importance of using concrete teaching aids inmathematics instruction at the junior high school level.